The Impact of Population Changes on Healthcare Demands using Nonhomogeneous Markov Model - บุราณศรี นวลพรรณ; จิตตะมัย พงษ์ชัย (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The study of the change of population structure is vital because there is continuous growth of number of elderly both in the national and the international. The purpose of this research is to study the effect of population change on the healthcare demand using nonhomogeneous Markov models to estimate the number of population and inpatients in the next ten years based on genders and age groups. The results show that 22 % of the population are likely to become the elderly in 2025 and the number of inpatients are increasing. This leads to the growing demand of long-term care and healthcare staff . This demand data can be used to prepare budgets for managing the change of resource requirement for long-term care management.